The excommunication of Elizabeth I: faith, politics, and resistance in post-Reformation England, 1570-1603 - Muller, Aislinn (St Andrews studies in Reformation history, 2020)
"This book grew out of a PhD dissertation that I began in 2013 at the University of Cambridge. I have been especially fortunate to have Alexandra Walsham as a mentor through all stages of this project, first as my graduate supervisor and throughout the process of turning my research into a book. I am indebted to her for all of her guidance"--